TEKNOLOGI DAN HUMANIORA DALAM KONTEKS PEMBANGUNAN - Sulistyaningsih, Tri (Jurnal Bestari, 1993)
Applying science and technology in national development is needed by Indonesian people. The implementation of science and technology will increase constanly on the Indonesian?s second long phase development, and in that time Indonesian will have been in the industrialization era. Consequently, as Indonesian people, we have to realize that transferring and applying science and technology is not only responsible of technologists, but it also involves other scientists.